Development and optimization of a PV/diesel hybrid supply system for remote controlled commercial large scale FM transmitters - Moghavvemi, Mahmoud; Ismail, M.S.; Murali, B.; Yang, S.S.; Attaran, A.; Moghavvemi, S. (Elsevier, 2013)
This paper is devoted to a renewable hybrid PV-diesel generator developed to supply power to a designated remote controlled FM transmitters located in remote locations. The developed system can guarantee the energy demand of the station (100% reliability) with less cost of energy production. In addition, this paper presents a remote control supervisory system designed to improve the entire transmitter-facilities processes which includes applications for sensing, managing, controlling and measuring transmitter site parameters and performance from a networked computer or a dial up computer. The need for detailed monitoring of the performance of transmitter site equipment including monitoring of electrical systems as well as monitoring of communication systems is becoming critical as these sites are becoming larger and more sophisticated. The systems was set up and tested through rigorous simulations of the transmitter site failures and evaluated for three consecutive months. The proposed systems have been installed and continuously operated on live FM transmitter facilities at six locations in Malaysia. The proposed hybrid power system can be also integrated into the current electric power network of Malaysia as a backup or as a main source of power for the entire transmitter facility. The supervision and control signals of the proposed power hybrid system can be easily included and integrated with the other existed FM transmitter supervisory and control signals. The concrete study in this paper is directed to one of the FM stations located in a remote area in Kuantan, Malaysia.